Effects of communication mode on EFL learners’ engagement and request learning - Shen, Zhiqi; Cheng, Cuiling (Frontiers in Education, 2024)
This study examines how different communication modes (two kinds of computer-mediated communication and face-to-face mode) influence EFL learners’ engagement during a collaborative writing task and its impact on subsequent request learning outcomes, measured by sociopragmatic and pragmalinguistic competence. Ninety-six high school English learners were assigned to groups for text-based chat, audio chat, and face-to-face interactions to complete a collaborative writing task in pairs. Two versions of the Written Discourse Completion Test (WDCT) were employed as pre-tests and post-tests to assess and compare the learning outcomes in request-making across the three groups. Cognitive and social engagement of learners were assessed by using multiple measures derived from chat logs and recordings, while a post-task questionnaire was utilized to gauge emotional engagement during the task. The results indicated that learners in the face-to-face and audio-chat conditions demonstrated higher levels of cognitive engagement compared to the text-chat group. The text-chat group reported fewer instances of negative emotions. In terms of request learning outcomes, all groups showed an increase in sociolinguistic appropriateness; however, no significant differences were found in overall pragmalinguistic competence. Social and emotional engagement significantly correlated with sociopragmatic improvement in the audio-chat mode, yet these indicators did not demonstrate significant predictive power.